Design And Characterization Of 20nm SOI MOSFET Doping Abruptness Dependent - Anis Suhaila, Mohd Zain; Nor Fatihah, Mohd Zain; Fauziyah, Salehuddin; N., Jamaluddin; N., Abdullah Yaacob (Asian Research Publishing Network (ARPN), 2016)
SOI MOSFET has currently become a trend for low power devices such as palmtops, cell phone, and other devices because it has a lot of advantage in terms of speed, density, and performance gain. Various efforts have been done to continue the progress in shrinking dimensions and higher-frequency performance will be driven by the market application. Reducing the size of SOI MOSFET will reduce the power, body effect, and parasitic capacitance, and increase the density and so on. This project focused mainly on the source/drain doping abruptness of SOI MOSFET. The doping abruptness was varied to find the best doping profile since the device was shrinking. In order to vary the source/drain doping abruptness, there were several problems to be encountered, which were increase in resistance, increase in threshold voltage, small sub-threshold slope, and others. The purpose of this project was to design the SOI MOSFET with an ideal doping profile and to investigate the impact on threshold voltage, current, and sub-threshold slope due to the variation of source/drain doping abruptness of SOI MOSFET. This project was designed using Silvaco Athena and Silvaco Atlas. Silvaco Athena was used to simulate the device structure and Silvaco Atlas was used to obtain the device characteristics of SOI MOSFET. This whole project was implemented on an SOI MOSFET doping abruptness dependent with a gate length of 21 nm.